2016
DOI: 10.2147/cia.s111097
|View full text |Cite
|
Sign up to set email alerts
|

Digital life storybooks for people with dementia living in care homes: an evaluation

Abstract: Background and aimThere is increasing interest in using information and communication technology to help older adults with dementia to engage in reminiscence work. Now, the feasibility of such approaches is beginning to be established. The purpose of this study was to establish an evidence-base for the acceptability and efficacy of using multimedia digital life storybooks with people with dementia in care homes, in comparison with conventional life storybooks, taking into account the perspectives of people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 26 publications
3
125
0
Order By: Relevance
“…(3) ways to incorporate difficult life events into the life story book; and (4) complex dynamics of hierarchy in the relationship between older couples and the interventionist Subramaniam and Woods (2016) Quantitative: Quality of life-Alzheimer's disease scale (QOL-AD); autobiographical memory interview extended version (AMI-E; subscales PSS and AIS); Geriatric Depression Scale Residential (GDS-12R); quality of the caregiving relationship questionnaire (QCPR). Qualitative: Open-ended questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) ways to incorporate difficult life events into the life story book; and (4) complex dynamics of hierarchy in the relationship between older couples and the interventionist Subramaniam and Woods (2016) Quantitative: Quality of life-Alzheimer's disease scale (QOL-AD); autobiographical memory interview extended version (AMI-E; subscales PSS and AIS); Geriatric Depression Scale Residential (GDS-12R); quality of the caregiving relationship questionnaire (QCPR). Qualitative: Open-ended questions.…”
Section: Discussionmentioning
confidence: 99%
“…In three studies, both a traditional and another type of LSB was formed, namely a digital book (Ingersoll-Dayton et al, 2016), a rummage box (Crook et al, 2016), and a pen picture (McKeown et al, 2013). In three studies, only a digital version was created: both studies by Hashim et al (2013; worked with a digital application and the study of Subramaniam and Woods (2016) used previously constructed tangible LSBs as input to create a digital life story movie. A wide variation of materials was used to create the LSBs: photographs, music, narration, stories, blank pages, quotations, and news items.…”
Section: Type and Characteristics Of The Life Story Booksmentioning
confidence: 99%
“…The most frequently reported type of engagement was through variously described communication such as interviews, focus groups, facilitated discussions, community consultation and workshops. Some older people worked practically alongside researchers to design and/or test 'products' for example a re-ablement system (Bond et al, 2015), a peer-education guide (Clarke et al, 2009), development of a home based dizziness intervention (Grönvall & Kyng, 2013) and a digital life-story book (Subramaniam & Woods, 2016).…”
Section: How Were Older People Engaged In Comethodological Working?mentioning
confidence: 99%
“…This review also found that although supporting resilience was beneficial to people with dementia, only a limited number of interventions have been developed and these have been assessed predominantly with people in early dementia in community settings who are currently "doing okay." Future research should focus on interventions that have the potential to support resilience through facilitating communication opportunities for people with more advanced dementia to interact with other people (58,71,72). Indeed, touchscreen technology has been found to enhance personhood of people with dementia (73) and robotic technologies can positively impact quality of life (74,75) and improve mood (76).…”
Section: Implications For Future Researchmentioning
confidence: 99%